EVALUATING THE PERFORMANCE AND SUSTAINABILITY OF INDUSTRIAL ESTATES IN ASSAM: A COMPREHENSIVE ANALYSIS USING THE IPRS FRAMEWORK - Das, Daisy; Ch Das , Tilak (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper evaluates the performance of 11 industrial infrastructural establishments in the Kamrup and Kamrup Metro districts of Assam, using the Industrial Park Rating System (IPRS) framework. The study focuses on four key pillars: internal infrastructure and utilities, external infrastructure and connectivity, business support services, and environment and safety management. Primary data was collected through structured questionnaires administered to MSME owners and managers, while secondary data was gathered from government reports and industrial policies. The findings reveal that while the basic infrastructure—such as uninterrupted power supply, piped water, and street lighting—is robust, significant gaps remain in advanced utilities, such as sewage treatment plants and renewable energy systems. Furthermore, inadequate business support services, including the absence of skill development centers and online land allotment systems, create operational challenges for MSMEs. Environmental and safety measures, such as disaster management protocols and rest areas for women workers, are also lacking. These deficiencies impact the overall efficiency and sustainability of the industrial estates. The study concludes with recommendations for enhancing both infrastructural quality and support services to foster a more competitive and sustainable industrial environment in Assam, thereby boosting MSME growth and economic development in the region.